A homozygous DSC2 deletion associated with arrhythmogenic cardiomyopathy is caused by uniparental isodisomy. (April 2020) - Brodehl, Andreas; Weiss, Jürgen; Debus, Jana Davina; Stanasiuk, Caroline; Klauke, Bärbel; Deutsch, Marcus André; Fox, Henrik; Bax, Jördis; Ebbinghaus, Hans; Gärtner, Anna; Tiesmeier, Jens; Laser, Thorsten; et al.
Abstract: Aims: We aimed to unravel the genetic, molecular and cellular pathomechanisms of DSC2 truncation variants leading to arrhythmogenic cardiomyopathy (ACM). Methods and results: We report a homozygous 4-bp DSC2 deletion variant c.1913_1916delAGAA, p.Q638LfsX647 hom causing a frameshift carried by an ACM patient. Whole exome sequencing and comparative genomic hybridization analysis support a loss of heterozygosity in a large segment of chromosome 18 indicating segmental interstitial uniparental isodisomy (UPD). Ultrastructural analysis of the explanted myocardium from a mutation carrier using transmission electron microscopy revealed a partially widening of the intercalated disc. Using qRT-PCR we demonstrated that DSC2 mRNA expression was substantially decreased in the explanted myocardial tissue of the homozygous carrier compared to controls. Western blot analysis revealed absence of both full-length desmocollin-2 isoforms. Only a weak expression of the truncated form of desmocollin-2 was detectable. Immunohistochemistry showed that the truncated form of desmocollin-2 did not localize at the intercalated discs. In vitro, transfection experiments using induced pluripotent stem cell derived cardiomyocytes and HT-1080 cells demonstrated an obvious absence of the mutant truncated desmocollin-2 at the plasma membrane. Immunoprecipitation in combination with fluorescence measurements and Western blot analyses revealed an abnormal secretion of the truncated desmocollin-2. Conclusion: In summary, we unraveled segmental UPD as the likely genetic reason for a small homozygous DSC2 deletion. We conclude that a combination of nonsense mediated mRNA decay and extracellular secretion is involved in DSC2 related ACM. Highlights: We show that DSC2 truncating mutations cause a loss of function mechanism. DSC2 truncating mutations can be recessively inherited. First report, demonstrating that uniparental isodisomy might be involved in ACM.